HLA-DR expression, cytokines and bioactive lipids in sepsis - Das, Undurti (Archives of medical science, 2014)
Sepsis accounts for more than 200,000 deaths annually in the USA alone. Both inflammatory and anti-inflammatory responses occur simultaneously in sepsis, the early phase dominated by the hyperinflammatory response and the late phase by immunosuppression. This late immunosuppression phase leads to loss of the delayed type hypersensitivity response, failure to clear the primary infection and development of secondary infections. Based on the available data, I hypothesize that failure to produce adequate amounts of inflammation resolving lipid mediators may be at the centre of both the hyperinflammatory response and late immunosuppression seen in sepsis. These proresolving lipids - lipoxins, resolvins and protectins - suppress exacerbated activation of leukocytes and macrophages, inhibit excess production of pro-inflammatory cytokines, initiate resolution of inappropriate inflammation, augment clearance of bacteria and other pathogens, and restore homeostasis. If true, this implies that administration of naturally occurring lipoxins, resolvins, protectins, maresins and nitrolipids by themselves or their more stable synthetic analogues such as 15-epi-16-(para-fluorophenoxy)-lipoxin A4-methyl ester, a synthetic analogue of 15-epi-lipoxin A4, and 15(R/S)-methyl-LXA4 may form a new approach in the prevention (in the high-risk subjects), management of sepsis and in resolving the imbalanced inflammatory process such that sepsis is ameliorated early. In addition, recent studies have suggested that nociceptin and cold inducible RNA binding protein (CIRBP) also have a role in the pathobiology of sepsis. It is suggested that both nociceptin and CIRBP inhibit the production of lipoxins, resolvins, protectins, maresins, and nitrolipids and thus play a role in sepsis and septic shock.